Prevalence of Hookworm infection and associated factors among Children below 14 years attending Outpatient Department at Kome Health Center III in Mukono District. A Cross-sectional Study. - Noordin, Katende; Nakalema , Margret (Student's Journal of Health Research Africa, 2022)
Background: Hookworm is one of the under-researched and neglected tropical diseases responsible for 90 million cases among children and in Uganda its degree is not well known. Methodology: A cross-sectional study was done at Kome health center III where 58 children were recruited between January and February using a simple random sampling method and tested for Hookworm infection. Additional data was obtained using Questionnaires to find out the associated factors and the most affected age among children below 14yrs. Data analysis was done using Microsoft Excel. Results: In the study, the sample size was 58 participants. Out of these, 6 /58 were infected giving a percentage of 10.3%, and the remaining 52 children were not infected with Hookworm. Children between 11-14 yrs. were the most affected (4/6) followed by those aged ≤5yrs and 6-10(16.7%) respectively. males were more infected than females. The infection was high among those who didn’t wash their hands, those who were not dewormed (6/6), and those who walked barefooted (4/6) cases of hookworm. All children attended from the rural areas Conclusion: The result of the study shows a relatively low prevalence of hookworm infection (10.3%) with children aged 11-14yrs being the most infected. Walking barefooted, failure to deworming, sex, residence, and age being the significantly associated with the prevalence of hookworm among these children Recommendation: To prevent the spread of hookworm among children, all children should first be screened extensively for the intestinal parasite to know the infection rate, mass deworming should be done to reduce the infection and transmission rate and the local government should encourage the construction of toilets or else construct more toilets for the community.